GAMBARAN ANGKA KEJADIAN Post Operative Nausea and Vomiting (PONV) DI RSUD ULIN BANJARMASIN MEI-JULI 2014 - Sholihah, Amalia; Sikumbang, Kenanga Marwan; Husairi, Ahmad (Jurnal Berkala Kedokteran, 2015)
Post operative nausea and vomiting (PONV) are defined as episode of nausea and emesis after a surgical act and before hospital discharge. Over 100 million patients undergo surgery in the worldwide with about 30% experiencing PONV. PONV have been associated with multifactorial such as age, gender, anaesthesia techniques, and type of surgery. The aim of this study was to determine the incidence of PONV in RSUD Ulin Banjarmasin May-July 2014. It was a descriftive study. Data was collected from a questioner on the first postoperative day. Consecutive sampling was used with a total of 96 patients as the subjects of this study. Of the 96 patients studied, 26 patients (27.08%) experienced PONV. The highest incidence of PONV occurred the age group 40-54 years with 11 patients (11.46%). Most of patients with PONV were female with 18 patients (18.75%). Based on the type of anaesthesia techniques used, those who were given general anaesthesia were the ones who mostly experienced PONV with 18 patients (18,75%). There were 12 patients (12.50%) who experienced PONV undergone digestive surgery. In conclusion, the highest incidence of ponv was found in the age group 40-54 years, female gender, patients who received general anaesthesia, and patients undergone digestive surgery.Â Keywords: post operative nausea and vomiting (PONV), age, gender, general anaesthesia techniques, type of surgery.